DISOBEDIENCE OF THE WIFE: ITS PROVISIONS AND EFFECTS ACCORDING TO THE LAW AND ISLAMIC LAW, A COMPARATIVE STUDY - Mahboba Mina; Thaer Muhammad Hussein Shukr; Luay ABED KAREEM (Scholar Express Journals, 2022)
The place of disobedience must be of great importance in family life. That is why Islam, with all its legislation, is keen to preserve family life and combat all behaviors that would destroy this intimacy between family members, especially with regard to what is between husband and wife, which is the main pillar of the family and its formation. Hastening to put in place the necessary measures to reform the family’s affairs when any dispute arises that would lead to a dispute between spouses to reduce the possibility of divorce and the dissolution of the family bond. Therefore, we discussed in the first section of this research the definition of disobedience and its cases in jurisprudence and law. As for the second topic, we referred to disciplinary measures. The wife and its effects, then the results and recommendations we reached, and God grant us success.
Keywords: Social; Civilized Or Cultural; Husband And Wife